Make biometric-based person identification system applicable - Hu, Yuanling. (2011)
Biometric based person identification technique attracts more and more attentions from research centers, businesses, government and military departments in recent years. It plays an important role in today’s society. Biometrics refers to the automatic recognition of a person through his/her physiological or behavioral traits such as face, fingerprint, DNA and palmprint. It is a combined use of the Digital Image Processing and Pattern Recognition technologies. To start off, a digital image is to be preprocessed so that some features can be extracted from it; and then the features are to be used to identify a person. While it is regarded as a relatively new field, palmprint recognition is a complement to the existing biometric technologies. The advantages of use one’s palmprint, a personal physiological trait for identification are many: uniqueness, abundance of information, and permanence, etc. Therefore, palmprint recognition starts to make more experts interested in it and research in this area.